Japan's financial crisis : Institutional rigidity and reluctant change - Amyx, Jennifer A. (Princeton University Press, 2004)
The book analyzes the decline of Japan's financial supervision since the 1990s following the asset bubble collapse. It highlights the Finance Ministry's deep influence in politics and finance, and how institutional structures affected change management. Political shifts and rising information demands led to the ministry's restructuring. The author questions how a once-successful system contributed to Japan's economic crisis.